DIGITAL COGNITIVE METRICS OF WRITTEN RESPONSES IN THE LONG LIFE FAMILY STUDY. (11th November 2018) - Sweigart, B; Andersen, S L; Wasserman, B; Cosentino, S; Wojczynski, M K; Au, R; Sebastiani, P; Perls, T T
Abstract: Digital pen data from cognitive test performance can be used to calculate metrics that may reflect aspects of cognition not captured in traditional scores. As poor test scores can be caused by slow cognition or slow writing, measuring the pauses between pen strokes may be a better indicator of cognitive speed. The Digit Symbol Substitution Test was completed by 584 Long Life Family Study subjects using a digital pen. We used R scripts to analyze time-stamped pen coordinate data, deriving total time, writing time, and pause time. Subjects spent a median of 61% (interquartile range 52–67%) of the test time paused and a median of 1.2 seconds (interquartile range 0.9–1.5 seconds) paused per symbol written. These extracted metrics allow for isolation of cognitive processing involved in Digit Symbol coding without confounding by motor slowing and provide data on change in cognitive processing demands across test time (90 seconds).